Comparison of observed and predicted MUF(3000)F2 in the polar cap region. Issue 6 (23rd June 2015) - Athieno, R.; Jayachandran, P. T.; Themens, D. R.; Danskin, D. W.
Abstract The maximum usable frequency for a 3000 km range circuit (MUF(3000)F2), computed from ionosonde measurements at Resolute (74.75∘N, 265.00∘E) and Pond Inlet (72.69∘N, 282.04∘E), has been compared with values obtained from the Ionospheric Communications Enhanced Profile Analysis and Circuit Prediction Program (ICEPAC), Voice of America Coverage Analysis Program (VOACAP), and International Telecommunication Union Recommendation 533 (REC533) models over a 4 year period. Predictions and observations show diurnal and seasonal variations; however, the VOACAP and ICEPAC models fail to reproduce the diurnal variation trend observed in the measurements during the summer period. The performance of these models has been statistically analysed: REC533 gives a better performance in winter and equinox months, while VOACAP has a better performance for both equinox and summer months. ICEPAC shows poor performance during low solar activity.